Zirconium-modified carbon-coated copper-zinc catalyst, preparation and application thereof in catalyzing CO2 to synthesize methanol
By coating the carbon layer on the surface of the copper-zinc catalyst and doping zirconium to form a zircon-coated copper-zinc catalyst, the oxidation and agglomeration inactivation of the catalyst active component Cu are solved, and the catalyst activity and stability are achieved. promote.
Patent Information
- Application Number
- CN202411595752.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-02-11
AI Technical Summary
The existing copper-zinc catalysts have problems with oxidation and agglomeration in methanol reaction of CO2 hydrogenation to synthesize the active component Cu, resulting in a decrease in the catalyst life and low conversion rate.
By covering the carbon layer on the surface of the copper-zinc catalyst and doping zirconium into the coating layer, a zirconium-modified carbon-coated copper-zinc catalyst is formed. This technical method improves catalyst activity through the abundant oxygen vacancy on the surface of the zirconium oxide, and inhibits Cu oxidation through the hydrophobic structure of the carbon layer.
The reactivity and stability of the catalyst are significantly improved, the service life of the catalyst is extended, and the CO2 conversion rate and methanol selectivity are improved.
Smart Images

Figure CN119406415A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a zirconium-modified carbon-coated copper-zinc catalyst and a preparation method and application thereof, and in particular to a catalyst suitable for CO 2 Zirconium-modified carbon-coated copper-zinc catalyst for methanol hydrogenation. Background Art
[0002] Currently, the rapid development of the global economy has led to the 2 ) emissions continue to rise, CO 2 The efficient recovery and utilization of CO shows great market potential. 2 Among the resource utilization approaches, CO 2 The hydrogenation methanol process is relatively simple and can draw on the mature process flow of syngas to methanol, significantly reducing the risk of industrial scale-up. 2 Hydrogen (H 2 ) to produce green methanol, which not only helps control greenhouse gas emissions, but can also further convert methanol into high-value-added chemical products through methanol to olefins, propylene, aromatics and other reactions. 2 Hydrogenation to synthesize methanol is a solution to the current CO 2 One of the effective ways to reduce emissions and fossil energy depletion.
[0003] CO 2 The hydrogenation reaction to methanol is thermodynamically feasible, but due to CO 2 The chemical properties of the molecule are stable, resulting in CO 2 Difficult to activate, CO 2 The conversion rate is extremely low, so the design and preparation of catalysts with high activity and catalytic performance is extremely important. At present, various precious metals (Pt, Pd and Rh) and non-precious metals (Cu, Co and Fe), carriers (ZnO, Al 2 O 3 and ZrO 2 ) and promoters (K, Ga, and Na) are used for CO 2 Research and application of hydrogenation to methanol reaction. Among them, copper-zinc-based catalysts have low cost and considerable activity and have been widely studied in methanol synthesis. Introducing additives on copper-zinc-based catalysts can provide more oxygen defects on the catalyst surface and improve CO 2activation ability. However, the existing preparation methods have some long-standing technical problems, such as the introduction of auxiliary components does not improve the overall activity of the catalyst, and the effect is not outstanding; or the catalyst still has particle agglomeration and deactivation, resulting in a decrease in the catalyst life; and after the existing catalyst is used, the long reaction process causes the active component Cu to easily agglomerate, and the water generated during the reaction causes the active component Cu to be oxidized and deactivated. Therefore, it is urgent to develop a CO catalyst with high catalytic activity and good catalytic reaction stability. 2 Catalyst for hydrogenation of methanol. Summary of the invention
[0004] The present invention proposes the concept of coating a carbon layer on the surface of a copper-zinc catalyst. On the one hand, zirconium is doped in the coating layer to enhance the activation of the catalyst. 2 On the other hand, the hydrophobic structure of the carbon layer on the catalyst surface inhibits the oxidation of the active component Cu caused by the contact between copper nanoparticles and the reaction by-product water, thereby improving the reaction activity and stability of the catalyst.
[0005] In order to achieve the above-mentioned purpose, the present invention adopts the following specific technical scheme.
[0006] A zirconium-modified carbon-coated copper-zinc catalyst, characterized in that: first, the copper-zinc catalyst is prepared by a coprecipitation method, then the copper-zinc catalyst is surface-modified by a zirconium salt aqueous solution containing a sugar, and then the surface-modified copper-zinc catalyst is subjected to a high-temperature carbonization treatment to obtain a hydrophobic zirconium-modified carbon-coated copper-zinc catalyst; the atomic ratio of copper, zinc and zirconium in the catalyst is (3-12): (3-6): 1.
[0007] Preferably, the zirconium salt is one of zirconium nitrate hydrate, zirconium oxynitrate, zirconium acetate, zirconium isopropoxide, or a mixture of any two or more thereof.
[0008] Preferably, the sugar is any one of glucose, mannose, fructose, maltose, sucrose and chitosan.
[0009] Preferably, the mass concentration of sugars in the zirconium salt aqueous solution is 5wt%~30wt%.
[0010] The method for preparing the zirconium-modified carbon-coated copper-zinc catalyst of the present invention comprises the following steps: S1. The copper salt and zinc salt mixed solution and the precipitant solution were uniformly mixed by a peristaltic pump under the premise of controlling the pH, aged for 3 hours, the obtained precipitate was centrifuged and washed, dried in an oven at 110 °C for 12 hours, and then the obtained dry sample was transferred to a muffle furnace, and calcined at 300-350 °C for 4-10 hours in an air atmosphere at a heating rate of 5 °C / min to obtain copper-zinc catalyst particles with a copper-zinc molar ratio of 1:1-4:1; S2. Weigh a certain amount of sugar compound and dissolve it in the zirconium salt solution. After fully mixing, add the copper-zinc catalyst particles obtained in step S1, stir vigorously at room temperature, then evaporate to dryness in an oil bath with stirring, and then put it into an oven and dry it at 100°C for 6 h. Then transfer the obtained dry sample to a tubular furnace, and in an inert atmosphere, calcine it at 300-450°C for 1-6 h at a heating rate of 2°C / min, crush and sieve to obtain a zirconium-modified carbon-coated copper-zinc catalyst with a particle size of 20-40 mesh.
[0011] Furthermore, in step S1, the copper salt is any one of copper nitrate trihydrate and copper acetate dihydrate; the zinc salt is any one of zinc nitrate hexahydrate and zinc acetate dihydrate; and the precipitant is any one of sodium carbonate or potassium carbonate.
[0012] Furthermore, in step S1, the pH is controlled by controlling the dropping speed of the precipitant solution so that the pH of the mixed system is maintained at 7.0±0.1.
[0013] Furthermore, in step S2, the stirring and evaporating under oil bath conditions is to control the temperature of the oil bath to 50°C-100°C and stir at a speed of 500 r / min to evaporate the water in the mixed system.
[0014] The zirconium-modified carbon-coated copper-zinc catalyst provided by the present invention is suitable for CO in a fixed bed reactor. 2 Hydrogenation methanol synthesis reaction process. When used, firstly, the zirconium-modified carbon-coated copper-zinc catalyst particles with a particle size of 20-40 meshes and quartz sand with the same mesh size are mixed and loaded into a reactor, and then the catalyst is reduced in a hydrogen atmosphere for 3-8 hours, and then switched to CO 2 / H 2 The reaction is carried out with a raw material gas having a molar ratio of 1:2 to 1:6. Preferably, the optimal reaction conditions are: reaction temperature 210 to 260°C, pressure 2.0 to 6.0 MPa, reaction space velocity 3000 to 12000 mL·h -1 ·g -1 .
[0015] The zirconium-modified carbon-coated copper-zinc catalyst and its preparation method and application of the present invention have the following substantial characteristics and improvements compared with the existing copper-zinc catalyst and its preparation method: During the preparation of the zirconium-modified carbon-coated copper-zinc catalyst of the present invention, zirconium is embedded in the C layer formed after the carbonization of the hydroxyl-rich carbon-containing compound, which can better anchor the zirconium nanoparticles and utilize the abundant oxygen vacancies on the surface of the zirconium oxide to improve the catalyst reaction activity. At the same time, the inventors also found that the original purpose of the technical solution of the present invention was to avoid the introduction of zirconium so that the copper-zinc catalyst forms a composite metal oxide during the high-temperature roasting process, thereby reducing the activity of the catalyst, so a technical route for constructing a thin film on the catalyst surface was designed. However, it was unexpectedly discovered during the research process that if the copper-zinc catalyst constructs a C layer and the zirconium nanoparticles are embedded in the C layer, the prepared catalyst can not only effectively inhibit the agglomeration of the catalyst, but also has hydrophobic properties, thereby avoiding the problem of the active component Cu being easily deactivated when it comes into contact with water.
[0016] As we all know, CO 2 In the hydrogenation reaction to synthesize methanol, the molar ratio of product methanol to byproduct water reaches 1:1. Byproduct water reacts with the active center Cu to cause the catalyst to deactivate. The surface hydrophobic C layer can greatly improve the stability of the catalyst and extend the service life of the catalyst. During the reaction, due to the hydrophobicity of the catalyst surface, water is difficult to adsorb on the catalyst surface, which is beneficial to avoid the occurrence of side reactions, thereby improving the selectivity of methanol. This is applied to CO 2 The design of copper-zinc catalysts with excellent activity and stability for the hydrogenation reaction to methanol provides a new strategy. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 The SEM image and line scan results of the catalyst in Example 1 are shown.
[0018] Figure 2 Comparison of contact angles of the catalysts of Example 1 and Comparative Example 1. DETAILED DESCRIPTION
[0019] The preparation method disclosed in this patent is further described below by specific examples, but the present invention is not limited to the following examples. [Example 1]
[0020] Take a certain amount of Cu(NO 3 ) 2 ·3H 2 O and Zn(NO 3 ) 2 6H 2 O and prepared into a 100 volume mixed solution with a substance concentration of 1.0 mol / L, in which the atomic ratio of Cu to Zn is 2:1, and 100 volume Na with a substance concentration of 1.0 mol / L is prepared at the same time. 2 CO 3solution, and then the two solutions were mixed in a beaker by a peristaltic pump, the pH of the solution was controlled to be 7.0±0.1, and then the precipitate was aged at room temperature for 3 h and centrifuged to wash until neutral, and then dried at 110 ℃ for 10 h, and the dried and ground sample was calcined at 310 ℃ in a muffle furnace at a heating rate of 5 ℃ / min for 4 h to obtain a copper-zinc catalyst.
[0021] Take a certain amount of chitosan and dissolve it in Zr(NO 3 ) 4 ·5H 2 O aqueous solution, and then added the copper-zinc catalyst powder prepared by the above method, controlling the carbon ratio to 10% and the copper-zinc-zirconium atomic ratio to 6:3:1, and then ultrasonically stirred for 30 min and stirred at room temperature for 6 h, and then stirred in a 60 ° C oil bath to evaporate the water, and then ground and transferred to a tubular furnace under Ar atmosphere and heated to 400 ° C at 2 ° C / min and maintained for 1 h to obtain a zirconium-modified carbon-coated copper-zinc catalyst. [Example 2]
[0022] Take a certain amount of Cu(CH 3 COO 2 ·H 2 O and Zn(CH 3 COO 2 ·(H 2 O) 2 A mixed solution with a molar concentration of 1.0 mol / L and a Cu to Zn atomic ratio of 3:1 was prepared in 100 volumes, and a K 2 CO 3 solution, and then the two solutions were mixed in a beaker by a peristaltic pump, the pH of the solution was controlled to be 7.0±0.1, and then the precipitate was aged at room temperature for 3 h and centrifuged to wash until neutral, and then dried at 110 °C for 6 h, and the dried and ground sample was calcined at 330 °C in a muffle furnace at a heating rate of 5 °C / min for 8 h to obtain a copper-zinc catalyst.
[0023] Take a certain amount of glucose and sucrose and dissolve them in ZrO(NO 3 ) 2 The copper-zinc catalyst powder prepared by the above method was then added to the aqueous solution, the carbon ratio was controlled to be 20% and the copper-zinc-zirconium atomic ratio was controlled to be 9:3:1, and then ultrasonic stirring was performed for 30 min and stirred at room temperature for 6 h, and then the water was evaporated by stirring in a 90 °C oil bath. After that, the mixture was ground and transferred to a tubular furnace and heated to 380 °C at 4 °C / min under an Ar atmosphere and maintained for 3 h to obtain a zirconium-modified carbon-coated copper-zinc catalyst. [Example 3]
[0024] Take a certain amount of Cu(NO 3 ) 2 ·3H 2 O and Zn(NO 3 ) 2 6H 2 O and prepared into a 100 volume mixed solution with a substance concentration of 1.0 mol / L, in which the atomic ratio of Cu to Zn is 3:2, and 100 volume Na with a substance concentration of 1.0 mol / L is prepared at the same time. 2 CO 3 solution, and then the two solutions were mixed in a beaker by a peristaltic pump, the pH of the solution was controlled to be 7.0±0.1, and then the precipitate was aged at room temperature for 3 h and centrifuged to wash until neutral, and then dried at 110 ℃ for 9 h, and the dried and ground sample was calcined at 340 ℃ in a muffle furnace at a heating rate of 5 ℃ / min for 5 h to obtain a copper-zinc catalyst.
[0025] Take a certain amount of glucose and dissolve it in C 12 H 28 O 4 Zr aqueous solution, and then add the copper-zinc catalyst powder prepared by the above method, control the carbon ratio to 15% and the copper-zinc-zirconium atomic ratio to 3:2:1, then ultrasonically stir for 30 min and stir at room temperature for 6 h, then use 65 °C oil bath to stir and evaporate the water, then grind and transfer to a tubular furnace under Ar atmosphere and heat at 3 °C / min to 340 °C and maintain for 6 h to obtain a zirconium-modified carbon-coated copper-zinc catalyst. [Example 4]
[0026] Take a certain amount of Cu(NO 3 ) 2 ·3H 2 O and Zn(NO 3 ) 2 6H 2 O and prepared into a 100 volume mixed solution with a substance concentration of 1.0 mol / L, in which the atomic ratio of Cu to Zn is 7:4, and 100 volume K with a substance concentration of 1.0 mol / L is prepared at the same time. 2 CO 3 solution, and then the two solutions were mixed in a beaker by a peristaltic pump, the pH of the solution was controlled to be 7.0±0.1, and then the precipitate was aged at room temperature for 3 h and centrifuged to wash until neutral, and then dried at 110 ℃ for 7 h, and the dried and ground sample was calcined at 335 ℃ in a muffle furnace at a heating rate of 5 ℃ / min for 7 h to obtain a copper-zinc catalyst.
[0027] Take a certain amount of maltose and dissolve it in C 12 H 28O 4 Zr aqueous solution, and then add the copper-zinc catalyst powder prepared by the above method, control the carbon ratio to 25% and the copper-zinc-zirconium atomic ratio to 9:3:1, then ultrasonically stir for 30 min and stir at room temperature for 6 h, then use 70 °C oil bath to stir and evaporate the water, then grind and transfer to a tubular furnace under Ar atmosphere and heat at 5 °C / min to 450 °C and maintain for 5 h to obtain a zirconium-modified carbon-coated copper-zinc catalyst. [Example 5]
[0028] Take a certain amount (CH 3 COO 2 Cu and Zn(NO 3 ) 2 6H 2 O and prepared into a 100 volume mixed solution with a substance concentration of 1.0 mol / L, in which the atomic ratio of Cu to Zn is 4:1, and 100 volume Na with a substance concentration of 1.0 mol / L is prepared at the same time. 2 CO 3 solution, and then the two solutions were mixed in a beaker by a peristaltic pump, and the pH of the solution was controlled to be 7.0±0.1. The precipitate was then aged at room temperature for 3 h and centrifuged to wash until neutral, and then dried at 110 °C for 8 h, and the dried and ground sample was calcined at 350 °C in a muffle furnace at a heating rate of 2 °C / min for 10 h to obtain a copper-zinc catalyst.
[0029] A certain amount of sucrose was dissolved in deionized water, and then the copper-zinc catalyst powder prepared by the above method was added, and the carbon proportion was controlled to be 30%. After ultrasonic stirring for 30 min and stirring at room temperature for 6 h, the water was evaporated by stirring in a 100 °C oil bath. After that, the mixture was ground and transferred to a tubular furnace under Ar atmosphere and heated to 350 °C at 2 °C / min and maintained for 4 h to obtain a zirconium-modified carbon-coated copper-zinc catalyst. [Comparative Example 1]
[0030] Take a certain amount of Cu(NO 3 ) 2 ·3H 2 O and Zn(NO 3 ) 2 6H 2 O and prepared into a 100 volume mixed solution with a substance concentration of 1.0 mol / L, in which the atomic ratio of Cu to Zn is 2:1, and 100 volume Na with a substance concentration of 1.0 mol / L is prepared at the same time. 2 CO 3solution, and then the two solutions were mixed in a beaker by a peristaltic pump, and the pH of the solution was controlled to be 7.0±0.1. The precipitate was then aged at room temperature for 3 h and centrifuged to wash until neutral, and then dried at 110 °C for 12 h, and the dried and ground sample was calcined at 300 °C in a muffle furnace at a heating rate of 5 °C / min for 4 h to obtain a copper-zinc catalyst. [Comparative Example 2] 3 ) 2 ·3H 2 O and Zn(NO 3 ) 2 6H 2 O and prepared into a 100 volume mixed solution with a substance concentration of 1.0 mol / L, in which the atomic ratio of Cu to Zn is 1:1, and 100 volume Na 2 CO 3 solution, and then the two solutions were mixed in a beaker by a peristaltic pump, and the pH of the solution was controlled to be 7.0±0.1. The precipitate was then aged at room temperature for 3 h and centrifuged to wash until neutral, and then dried at 110 ℃ for 12 h, and the dried and ground sample was calcined at 350 ℃ in a muffle furnace at a heating rate of 5 ℃ / min for 6 h to obtain a copper-zinc catalyst.
[0031] Take a certain amount of Zr(NO 3 ) 4 ·5H 2 O was dissolved in an aqueous solution, and then the copper-zinc catalyst powder prepared by the aforementioned method was added to control the copper-zinc-zirconium atomic ratio to be 3:3:1. The mixture was then ultrasonically stirred for 30 min and stirred at room temperature for 6 h, and then the water was evaporated by stirring in a 50 °C oil bath. The mixture was then ground and transferred to a tubular furnace and heated to 350 °C at 5 °C / min under an Ar atmosphere and maintained for 4 h to obtain a zirconium-modified carbon-coated copper-zinc catalyst. [Comparative Example 3]
[0032] Take a certain amount of Cu(NO 3 ) 2 ·3H 2 O and Zn(NO 3 ) 2 6H 2 O and prepared into a 100 volume mixed solution with a substance concentration of 1.0 mol / L, in which the atomic ratio of Cu to Zn is 2:1, and 100 volume Na with a substance concentration of 1.0 mol / L is prepared at the same time. 2 CO 3solution, and then the two solutions were mixed in a beaker by a peristaltic pump, and the pH of the solution was controlled to be 7.0±0.1. The precipitate was then aged at room temperature for 3 h and centrifuged to wash until neutral, and then dried at 110 ℃ for 12 h, and the dried and ground sample was calcined at 320 ℃ in a muffle furnace at a heating rate of 5 ℃ / min for 6 h to obtain a copper-zinc catalyst.
[0033] A certain amount of maltose was dissolved in deionized water, and then the copper-zinc catalyst powder prepared by the above method was added, and the carbon proportion was controlled to be 5%. After ultrasonic stirring for 30 min and stirring at room temperature for 6 h, the water was evaporated by stirring in an 80 °C oil bath. After that, the mixture was ground and transferred to a tubular furnace and heated to 300 °C at 2 °C / min under Ar atmosphere and maintained for 2 h to obtain a zirconium-modified carbon-coated copper-zinc catalyst.
Catalyst structure characterization
[0034] Figure 1 The SEM image and line scan results of the catalyst in Example 1 are shown in FIG. Figure 1 From the line scanning results, it can be seen that the changes in the content of Zr and C on the surface of the zirconium-modified carbon-coated copper-zinc catalyst confirm the coating structure on the surface of the zirconium-modified carbon-coated copper-zinc catalyst. Figure 2 The contact angle data of the catalysts of Example 1 and Comparative Example 1 show that the hydrophobicity of the zirconium-modified carbon-coated copper-zinc catalyst is significantly better than that of the unmodified catalyst, which illustrates the formation of a hydrophobic C layer. The contact between the byproduct water and the active component Cu in the catalyst can be suppressed during the reaction, which helps to avoid the oxidation of Cu and improve the stability of the catalyst. By changing different hydroxyl-rich carbon-containing compounds, the degree of carbon coating on the surface of the catalyst can be affected, and thus the hydrophobicity of the surface C layer can also be affected. After comparison, it is found that chitosan is used as a carbon source, and the hydrophobic property of the catalyst is the best. Since the catalysts prepared in Examples 2 to 5 of the present invention have similar SEM images and hydrophobic properties, they are not listed here one by one.
Catalyst performance test
[0035] In order to test the catalytic activity, stability and other properties of the catalyst prepared by the method of the present invention, the catalysts provided in Examples 1 to 5 and Comparative Examples 1 to 3 were reacted in a fixed bed reactor for 100 hours. 2 Conversion rate, methanol selectivity and catalyst deactivation rate tests.
[0036] During the test, the amount of catalyst added was 0.15 g-0.5 g. The catalyst was pressed into tablets and sieved in the range of 20-40 mesh before filling. It was mixed with quartz sand of the same mesh size during filling. The products in the reaction process were analyzed online by gas chromatography. The operation process and process parameters are: the reaction space velocity is controlled at 3000-12000 mL·h by controlling the flow rate of the raw gas. -1 ·g-1 Range; temperature is raised under inert gas, and hydrogen-inert gas mixture is switched to reduction for 3-8 h, after which the inert gas is purged down to the reaction temperature of 210 ℃~260 ℃, the inert gas back pressure is 2.0 MPa~6.0 MPa, and CO is switched to 2 / H 2 / Ar composed of raw gas to replace inert gas, in which CO 2 / H 2 The specific process parameters and catalyst performance test results of each embodiment and comparative example are shown in Table 1. Table 1
[0037] project Hydrogen-carbon molar ratio Reaction temperature / ℃ Reaction pressure / MPa <![CDATA[Reaction space velocity / mL·g -1 ·h-1]]> <![CDATA[CO 2 Conversion rate (%)]]> <![CDATA[CH 3 OH selectivity (%)]]> Inactivation rate (%) Example 1 3:1 220 4 3000 10.2 85.3 26.4 Example 2 2:1 240 5 9000 9.4 82.2 34.4 Example 3 4:1 250 4 4500 9.9 75.7 29.5 Example 4 2:1 230 3 7200 9.1 76.5 28.1 Example 5 3:1 250 6 12000 9.2 82.8 30.8 Comparative Example 1 3:1 220 4 3000 6.1 63.2 48.2 Comparative Example 2 3:1 250 6 12000 8.6 48.5 46.3 Comparative Example 3 2:1 240 5 9000 8.1 76.1 38.6 .
[0038] It can be seen from Table 1 that the introduction of zirconium modification into copper-zinc catalyst alone can improve CO 2 conversion rate, proving that zirconium modification can better activate CO 2 To improve the activity of the catalyst. The deactivation rates of copper-zinc catalysts and copper-zinc-zirconium catalysts without the introduction of carbon were as high as 48.2% and 46.3%. Using different hydroxyl-rich carbon-containing compounds as carbon sources, the hydrophobic carbon layer formed after carbonization can inhibit both catalyst agglomeration and water oxidation of the catalyst active center, which is the reason for the improved stability. After comparing different hydroxyl-rich carbon-containing compounds, it was found that the catalyst deactivation rate dropped to 26.4% after the introduction of chitosan. The above results show that zirconium modification can significantly improve the activity of the catalyst, and the choice of hydroxyl-rich carbon-containing compounds directly affects the stability of the catalyst. The thickness of the surface carbon layer can also affect the effective active center of the catalyst, and the effect of the carbon layer on the hydrophobicity of the catalyst also directly affects the methanol selectivity. This is because water is difficult to adsorb on the catalyst surface, which can avoid the occurrence of side reactions and thus improve the methanol selectivity.
Claims
1. A zirconium-modified carbon-coated copper-zinc catalyst, characterized in that: First, a copper-zinc catalyst is prepared by a coprecipitation method, and then the copper-zinc catalyst is surface-modified using a zirconium salt aqueous solution containing a sugar. The surface-modified copper-zinc catalyst is then subjected to a high-temperature carbonization treatment, crushed, and sieved to obtain a zirconium-modified carbon-coated copper-zinc catalyst with a particle size of 20-40 meshes; the atomic ratio of copper, zinc, and zirconium in the catalyst is (3-12): (3-6):
1.
2. The zirconium-modified carbon-coated copper-zinc catalyst according to claim 1, characterized in that: The zirconium salt is one of zirconium nitrate hydrate, zirconium oxynitrate, zirconium acetate, zirconium isopropoxide, or a mixture of any two or more thereof.
3. The zirconium-modified carbon-coated copper-zinc catalyst according to claim 1, characterized in that: The sugar is any one of glucose, mannose, fructose, maltose, sucrose and chitosan.
4. The zirconium-modified carbon-coated copper-zinc catalyst according to claim 1 or 3, characterized in that: The mass concentration of sugar in the zirconium salt aqueous solution is 5wt%-30wt%.
5. A method for preparing the zirconium-modified carbon-coated copper-zinc catalyst according to any one of claims 1 to 4, comprising the following steps: S1. The copper salt, zinc salt mixed solution and the precipitant solution were uniformly mixed by a peristaltic pump under the premise of controlling the pH, aged for 3 hours, the obtained precipitate was centrifuged and washed, dried in an oven at 110 °C for 12 hours, and then the obtained dry sample was transferred to a muffle furnace, and calcined at 300-350 °C for 4-10 hours in an air atmosphere at a heating rate of 5 °C / min to obtain a copper-zinc catalyst with a copper-zinc molar ratio of 1:1-4:1; S2. Weigh a certain amount of sugar compound and dissolve it in the zirconium salt solution. After fully mixing, add the copper-zinc catalyst obtained in step S1, stir at room temperature until the mixture is uniformly mixed, and then evaporate to dryness under oil bath conditions, and then put it into an oven and dry it at 100°C for 6 h. Then transfer the obtained dry sample to a tubular furnace, and in an inert atmosphere, calcine it at 300-450°C for 1-6 h at a heating rate of 2°C / min, crush and sieve to obtain a zirconium-modified carbon-coated copper-zinc catalyst with a particle size of 20-40 mesh.
6. The method for preparing the zirconium-modified carbon-coated copper-zinc catalyst according to claim 5, characterized in that: In step S1, the copper salt is any one of copper nitrate trihydrate and copper acetate monohydrate; the zinc salt is any one of zinc nitrate hexahydrate and zinc acetate dihydrate; and the precipitant is any one of sodium carbonate or potassium carbonate.
7. The method for preparing the zirconium-modified carbon-coated copper-zinc catalyst according to claim 5, characterized in that: In step S1, the pH is controlled by controlling the dropping speed of the precipitant solution so that the pH of the mixed system is maintained at 7.0±0.
1.
8. The preparation method according to claim 5, characterized in that: In step S2, the stirring and evaporating under oil bath conditions is to control the temperature of the oil bath to 50°C-100°C and stir at a speed of 500 r / min to evaporate the water in the mixed system.
9. The zirconium-modified carbon-coated copper-zinc catalyst according to any one of claims 1 to 4 is used to catalyze the CO2 hydrogenation to methanol synthesis reaction in a fixed bed reactor.
10. The use according to claim 9, characterized in that Before the reaction, the zirconium-modified carbon-coated copper-zinc catalyst is first reduced in a hydrogen atmosphere for 3 to 8 h, and then switched to a feed gas with a CO2 / H2 molar ratio of 1:2 to 1:6 for catalytic reaction. The reaction conditions are: reaction temperature 210 to 260°C, pressure 2.0 to 6.0 MPa, reaction space velocity 3000 to 12000 mL·h -1 ·g -1 .
Citation Information
Cited By
Preparation method and application of catalyst for preparing methanol through hydrogenation of carbon dioxide
CN121911460A